MASA DEPAN ANAK MUDA PERTANIAN DI TENGAH LIBERALISASI PERTANAHAN - Ahmad Nashih Luthfi; Surya Saluang (BHUMI: Jurnal Agraria dan Pertanahan, 2015)
Abstract: The opitimism and persistence of small farmers, such as Alexander Chayanov’s view, need to be thoroughly exploredby examining the demographic composition of the farmers’ families, especially those of their younger genarations. The paperis aimed at finding the critical existance of the Indonesian agricultural regeneration caused by the structural constraints. Theycan be in the form of political large-sacle land alocation for corporates; and other stuctural patriarchal and grontocraticconstraints; instead of the young generations’ motivation. If the above constraints are able to be eliminated, as two cases inHalmahera islands and one village in Kulonprogo regency, Yogyakarta, there will be large opportunity for them. The youths’enthusiasm will grow if there is an open access for them. The access can be in the form of land, work opportunity, knowledge onagriculture as well as agricultural policy for household-scale.Keywords: youth farming generation, alocation policy, patriarchal and grontocratic cultures, access.Abstrak: Optimisme peran dan persistensi petani kecil sebagaimana pandangan Alexander Chayanov perlu lebih didalami denganmelihat komposisi demografis keluarga masyarakat tani, khususnya generasi muda mereka. Tulisan ini mengkaji adanya krisisregenerasi pertanian Indonesia yang lebih disebabkan adanya kendala-kendala struktural berupa politik pengalokasian tanahskala besar untuk korporasi; dan kendala kultural yang bersifat patriarkis dan grontokratis; alih-alih absennya motivasi generasimuda. Ketika kendala-kendala tersebut dapat dihilangkan, sebagaimana yang ditunjukkan dalam kasus di dua desa di kepulauanHalmahera dan satu desa di Kulonprogo, Yogyakarta, maka terbuka peluang besar keterlibatan mereka. Antusiasme generasimuda akan tumbuh ketika segenap akses terbuka luas bagi mereka, yakni berupa tanah, keterbukaan tenaga kerja, pengetahuanpertanian, serta kebijakan pertanian skala rumah tangga.Kata kunci: generasi muda pertanian, politik alokasi, budaya patriarkis dan grontokratis, akses